Intelligent system development of distant matrix analysis for recruitment in the IT sector - Kutyuk Orest; Lytvyn Vasyl; Oborska Oksana; Vysotska Victoria; Dosyn Dmytro; Demchuk Andriy; Burov Yevhen; Kravets Petro (онлайн, 2020)
Development of intelligent system matrix analysis distant for recruitment in the IT sector. To achieve the goal must perform the following tasks:  to conduct a study of the literature and identify which ones are best suited to the subject of work;  to conduct a study of existing software and decide which ones are relevant to the theme of work;  perform system analysis about ‘the object of the study;  develop optimal solutions for tasks;  design and develop a software interface to work with the client system;  develop an algorithm to calculate customer data systems;  design and develop a software interface for visualization client system. Object of research is analysis distant knowledge. Subject of study is intelligent analysis matrix distant for recruitment in the IT sector. The paper improved analysis algorithm multicriterion TOPSIS, which can significantly improve the accuracy of the assessment. Output can be used to simplify the process of finding and hiring candidates of IT recruiters and get them a full analysis of the relevant knowledge distant positions.
Keywords: content, commercial content, information resource, business process, content management system, content lifecycle, Internetnewspaper, electronic content commerce system, Virtual Library